Arbitrage pricing theory - Gur Huberman (Federal Reserve Bank of New York, 2005)
Focusing on capital asset returns governed by a factor structure, the Arbitrage Pricing Theory (APT) is a one-period model, in which preclusion of arbitrage over static portfolios of these assets leads to a linear relation between the expected return and its covariance with the factors. The APT, however, does not preclude arbitrage over dynamic portfolios. Consequently, applying the model to evaluate managed portfolios is contradictory to the no-arbitrage spirit of the model. An empirical test of the APT entails a procedure to identify features of the underlying factor structure rather than merely a collection of mean-variance efficient factor portfolios that satisfies the linear relation.
Keywords: G12; 330; arbitrage; asset pricing model; factor model; Arbitrage Pricing; Capital Asset Pricing Model; Theorie